Relationship between Customer Engagement and Loyalty with Usage of Mobile Banking - Pernamawati, Supriati Nugroho; Prambudi, Agung; Irfan, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to understand the relationship between customer engagement, loyalty, and mobile banking usage can provide valuable insights for banks in improving customer relationships, increasing customer satisfaction, and driving business growth. This research is included in descriptive quantitative research. The data analysis technique used in this study was Partial Least Square (PLS). This research was conducted at Bank Muamalat Indonesia, Region Surabaya. The sampling technique in this study was purposive sampling, so in this study, the research sample was 100 customers of Bank Muamalat Indonesia, Region Surabaya. The results showed that the usage of mobile banking was influenced by customer engagement and loyalty by 62.6%, and the rest was influenced by variables that have not been explained in this study. It can be concluded that mobile banking users show engagement from employees who are interested in the bank and loyalty from customers.